Sefarad but not Spain : the settlement of Jews in Gibraltar, 1704-1783 - Madway, Lorraine (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 1993)
Jews arrived in Gibraltar shortly after a combined force of English and Dutch soldiers occupied the Rock in 1704, during the War of Spanish Succession. Most of them were descendants of «gerushim» who left Spain in 1492 and went to northern Morocco. The struggle of Jews to settle and establish a community in Gibraltar parallels and, indeed, is a result of the struggle of the British to control the fortress whose strategic position they had long appreciated. Initially, Jewish merchants and interpreters made themselves useful by providing commercial and diplomatic services to the garrison that no one else could provide. Just as the British occupation withstood the test of repeated Spanish assaults during the course of the eighteenth century, so too, did Jews manage to rebuff the periodic attempts of British governments to remove them. Through service and persistence, Jews finally won the right to settle in the town and establish a community. The presence of a flourishing Sephardic community within plain view of Spain’s shores is surely one of the ironies of Spanish-Jewish history which makes its study a subject of continuing fascination.